Apresiasi Seni Masyarakat Primitif Suku Asmat dalam Roman "Namaku Tewerawut" Karya Ani Sekarningsih - Ummu Fatimah Ria Lestari (Kibas Cenderawasih : Jurnal Ilmiah Kebahasaan dan Kesastraan, 2019)
Namaku Tewerawut is a roman tells about Asmat people in Papua. It was written by Ani Sekarningsih and published in 2000. The researcher interested to analyze about appreciating arts of the Asmat people because no research about it before. Based from Namaku Tewerawut roman, Asmat people are animism and dynamism. Its religion system influences their appreciation to arts values. Their arts appreciation was drawn by the author in description method. So it had described page by page, paragraph by paragraph, and word by word to analyze that parts. The conclusion of this research is the religion system of Asmat can we see on their arts appreciating.